Анализ вибровозмущающих осевых сил в сердечнике статора мощного турбогенератора - Васьковский, Юрий Николаевич; Шумилов, Юрий Андреевич; Штогрин, Александр Валерьевич (НТУ "ХПИ", 2009)
Выполнен анализ вибровозмущающих осевых сил в сердечнике статора мощного турбогенератора па примере анализа причин разрушения его стяжных шпилек. Показано, что их разрушение происходит из-за усталости материалов шпилек при многоциклическом погружении. Разработаны методики расчета сил, основанные на методах механики разрушения и теории электромагнитного поля.

Analysis of vibration-exciting axial forces in a powerful turbo-generator stator core has been carried out by considering the causes responsible for its coupling studs destruction. It is shown that the destruction is caused by fatigue of coupling stud materials resulting from high-cycle loading. Techniques of calculating the forces have been developed on the basis of destruction mechanics methods and the theory of electromagnetic field.
Analysis of vibration-exciting axial forces in a powerful turbo-generator stator core
Keywords: методы механики разрушения; теория электромагнитного поля; стяжные шпильки; атомные электростанции; powerful turbo-generator stator core; vibration-exciting axial forces; analysis; calculation technique